Stakeholders in Mt. Elgon region agree to use local legislation to improve coffee quality - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
The Mbale district climate change Learning alliance established by the CCAFS sponsored Policy Action for Climate Change Adaptation project, after going through a series of participatory identification of challenges, prioritized the coffee ordinance given the number of people that depend on the crop. The district local government aims at regulating the coffee value chain from seed systems to processing. The ordinance will be implemented by private and public sector partners together with that farming community with each having clear roles.